IMPLEMENTASI WEBSITE FAKULTAS DAKWAH DAN KOMUNIKASI SEBAGAI MEDIA DAKWAH DAN PROMOSI - Muhayat, Muhayat (Alhadharah: Jurnal Ilmu Dakwah, 2015)
The website is a new media that is very popular today, and to be very important is implemented by individuals and institutions in order to take advantage as the Company Presence, Product / Service Communication, Prospect / Client Entry Door, Increase Company Image. Faculty of Da'wa and Communication IAIN Antasari has implemented a website that has a URL (Uniform Resource Identifier) http://dakwah.iain-antasari.com and based on the results of the study authors, the website has been able to become a medium of information and media propaganda and promotion. This website is implemented using the System Development Life Cycle (SDLC) to the stages of implementation starting from Conception, Initiation, Analysis, Design, Construction, Testing, and Deployment. With the implementation of the website is expected to improve the image of the institution as well as a medium of propaganda and promotion of effective and efficient.Website merupakan media baru yang sangat populer saat ini, dan menjadi sangat penting diimplementasikan oleh individu maupun lembaga dalam rangka mengambil manfaat sebagai Company Presence, Product/Service Communication, Prospect/Client Entry Door, Increase Company Image. Fakultas Dakwah dan Komunikasi IAIN Antasari telah mengimplementasikan sebuah website yang memiliki URL (Uniform Resource Identifier) http://dakwah.iain-antasari.com dan berdasarkan hasil telaah penulis, website tersebut telah mampu menjadi media informasi sekaligus media dakwah dan promosi. Website ini diimplementasikan menggunakan metode System Development Life Cycle (SDLC) dengan tahapan implementasi dimulai dari Conception, Initiation, Analysis, Design, Construction, Testing, dan Deployment. Dengan telah diimplementasikannya website tersebut diharapkan dapat meningkatkan image lembaga sekaligus menjadi media dakwah dan promosi yang efektif dan efisien.